Study of the Effects of 3 h of Continuous Cardiopulmonary Resuscitation at 27°C on Global Oxygen Transport and Organ Blood Flow - Nilsen, Jan Harald; Valkov, Sergei; Mohyuddin, Rizwan; Schanche, Torstein; Kondratiev, Timofei V.; Naesheim, Torvind; Sieck, Gary C.; Tveita, Torkjel (Frontiers in Physiology, 2020)
Aims: Complete restitution of neurologic function after 6h pre-hospital resuscitation and in-hospital rewarming has been reported in accidental hypothermia patients with cardiac arrest (CA). However, the level of restitution of circulatory function during long-lasting hypothermic cardiopulmonary resuscitation (CPR) remains largely unknown. We compared the effects of CPR in replacing spontaneous circulation during 3h at 27°C versus 45 min at normothermia by determining hemodynamics, global oxygen transport (DO2), oxygen uptake (VO2), and organ blood flow. Methods: Anesthetized pigs (n=7) were immersion cooled to CA at 27°C. Predetermined variables were compared: 1) Before cooling, during cooling to 27°C with spontaneous circulation, after CA and subsequent continuous CPR (n=7), versus 2) Before CA and during 45-min CPR in normothermic pigs (n=4). Results: When compared to corresponding values during spontaneous circulation at 38°C: 1) After 15 min CPR at 27°C, cardiac output (CO) was reduced by 74 %, mean arterial pressure (MAP) by 63 %, DO2 by 47 %, but organ blood flow was unaltered. Continuous CPR for 3h maintained these variables largely unaltered except for significant reduction in blood flow to heart and brain after 3h, to kidneys after 1h, to liver after 2h, and to stomach and small intestine after 3h. 2) After normothermic CPR for 15 min, CO was reduced by 71 %, MAP by 54 %, and DO2 by 63 %. After 45 min, hemodynamic function had deteriorated significantly, organ blood flow was undetectable, serum lactate increased by a factor of 12, and mixed venous O2 content was reduced to 18 %. Conclusions: The level to which CPR can replace CO and MAP during spontaneous circulation at normothermia was not affected by reduction in core temperature in our setting. Compared to spontaneous circulation at normothermia, 3h continuous resuscitation at 27°C provided limited but sufficient O2 delivery to maintain aerobic metabolism. This fundamental new knowledge is important in that it encourages early and continuous CPR in accidental hypothermia victims during evacuation and transport.